Evaluation of clinical approaches and physician adherence to guidelines for otitis media with effusion. (September 2018) - Cullas Ilarslan, Nisa Eda; Gunay, Fatih; Topcu, Seda; Ciftci, Ergin
Abstract: Objectives: Otitis media with effusion (OME) is an important clinical entity because of its high prevalence, difficulties in diagnosis, complications and diversities in management. Herein, we aimed to evaluate current physician approaches on OME and determine clinical adherence to current guidelines. Methods and materials: A total of 370 physicians [Group 1: pediatricians (n = 256, 69.2%), Group 2: otorhinolarynologists (n = 114, 30.8%)] completed a survey instrument addressing demographic data and clinical practice parameters on OME in children. We also compared clinical approaches of Group 1 and Group 2. In addition, multiple logistic regression analysis was performed to evaluate factors which may effect correct approaches. Results: The mean period of clinical experience was 9.30 ± 8.35 [median 6 (1–40)] years. A total of 311 (84%) respondents reported satisfactory level of self-confidence as regards of clinical approaches to OME. Reduced mobility of the tympanic membrane and preference of pneumatic otoscopy was signified by 107 (28.9%) and 64 (17.3%) respondents, respectively. Fifty-six (15.1%) physicians identified "watchful waiting" for 3 months for children who are not at risk while 314 (84.9%) reported preference of medications, with antibiotics the most preferred prescription (n = 223, 63%). Comparison of Group 1 and Group 2 indicated similar results except better, yet insufficient, characterization of physical examination findings of OME by Group 2 (p < 0.001, for each parameter). Group 2 preferred tympanometry more in uncertain cases (p < 0.001) and handled chronic cases better (p < 0.001). Multiple logistic regression analysis revealed lower signification of reduced mobility of the tympanic membrane for respondents who denoted depending on personal experience ([OR] = 3.077 [95% CI 1.042–9.09]) or following clinical guidelines ([OR] = 3.365 [95% CI 1.38–8.20]) rather than combining them both. Rate of antibiotic avoidance was lowest in physicians with a period of clinical experience<5 years ([OR] = 2.14 [95% CI 1.32–3.48]). Conclusions: Despite notifying high self-confidence and adherence to current guidelines on OME, both pediatricians and otorhinolaryngologists lacked to exhibit proper approaches. Further research is warranted to evaluate the causes of poor adherence to current guidelines and bring suggestions for the maintenance of consistent and correct clinical approaches to OME.